(untitled) (International Journal of Innovative Technologies in Economy, 2026)
Corruption, as an exceptional crime, results in enormous state financial losses and obstructs national development. Indonesia’s asset forfeiture regime, however, remains anchored in a conviction-based model that presupposes a final, binding criminal judgment which is a precondition that significantly undermines effective asset recovery. Addressing this gap, the current research aims to critically evaluate the performance of existing loss-recovery instruments and to propose an optimal regulatory design for non-conviction based (NCB) asset forfeiture in Indonesia. Methodologically, this is a normative legal study incorporating statutory, conceptual, and comparative approaches. Legal materials including primary, secondary, and tertiary are examined qualitatively using a descriptive-analytical framework. The findings indicate that the existing asset forfeiture mechanism still faces various obstacles, including dependence on criminal prosecution, limited scope of forfeitable objects, weak inter-agency coordination, and a suboptimal asset tracing system. Moreover, the proportion of state losses actually recovered continues to lag significantly behind the aggregate losses incurred. Evidence drawn from comparative analysis with the United States and the United Kingdom indicates that the NCB model yields superior effectiveness by virtue of its in rem orientation which targeting the assets directly and its elimination of any prerequisite for securing a criminal conviction against the offender. Therefore, a reconstruction of Indonesia’s legal system is needed through the establishment of specific regulations governing asset forfeiture without criminal conviction, strengthening of asset management institutions, enhancement of international cooperation, and optimization of technology in asset tracing. Accordingly, the implementation of NCB is expected to improve the effectiveness of state loss recovery and strengthen the corruption eradication system in Indonesia.